2019
DOI: 10.1007/978-3-030-33778-0_11
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Traffic Prediction and Classification: A Comparative Evaluation of LSTM and ARIMA

Abstract: Prediction of user traffic in cellular networks has attracted profound attention for improving resource utilization. In this paper, we study the problem of network traffic traffic prediction and classification by employing standard machine learning and statistical learning time series prediction methods, including long short-term memory (LSTM) and autoregressive integrated moving average (ARIMA), respectively. We present an extensive experimental evaluation of the designed tools over a real network traffic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 34 publications
0
42
0
Order By: Relevance
“…Publicly available data set: We also evaluate the metalearning scheme on four data sets created from the Wireshark traces collected and analyzed in [19], available on GitHub. The data set contains cellular uplink and downlink traffic, of which we only considered the downlink traffic.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Publicly available data set: We also evaluate the metalearning scheme on four data sets created from the Wireshark traces collected and analyzed in [19], available on GitHub. The data set contains cellular uplink and downlink traffic, of which we only considered the downlink traffic.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In general, each data set spans over tens of thousands of prediction intervals. In addition we evaluated the predictors on four publicly available data sets reported in [19]. In the appendix, Table IV provides a summary of the data sets.…”
Section: B Evaluation Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, LSTM is ready to process multivariate time series. The authors of [35] and [36] revealed that, the higher the number of input variables, the better the traffic predictions of LSTM when compared to ARIMA.…”
Section: B Time Series For Network Traffic Forecastmentioning
confidence: 99%